Stable governments and the semistrict core. Revised version of 'Coalition formation in simple games: the semistrict core' - Dinko Dimitrov; Claus-Jochen Haake (Bielefeld University, Institute of Mathematical Economics (IMW), 2006)
We consider the class of proper monotonic simple games and study coalition formation when an exogenous weight vector and a solution concept are combined to guide the distribution power within winning coalitions. These distributions induce players' preferences over coalitions in a hedonic game. We formalize the notion of semistrict core stability, which is stronger than the standard core concept but weaker than the strict core notion and derive two characterization results for the semistrict core, dependent on conditions we impose on the solution concept. It turns out that a bounded power condition, which connects exogenous weights and the solution, is crucial. It generalizes a condition termed 'absence of the paradox of smaller coalitions' that was previously used to derive core existence results.
urn:nbn:de:hbz:361-9850
Keywords: D72; C71; 330; Coalition formation; Semistrict core; Simple games; Winning coalitions; Koalition; Spieltheorie; Core; Theorie